Psychometric properties of the Arabic version of EPDS and BDI-II as a screening tool for antenatal depression: evidence from Qatar - Sarah Naja; Noora Al-Kubaisi; Mohamad Chehab; Nada Abuhashem; Iheb Bougmiza (BMJ Open)
Objectives The current study aimed to validate and determine the psychometric properties of the Arabic versions of the Beck Depression Inventory-II (BDI-II) and the Edinburgh Postnatal Depression Scale (EPDS) in Qatar.Design A cross-sectional study design was employed.Setting Antenatal care (ANC) clinics at nine primary healthcare centres.Participants Pregnant women (n=128) aged 15–46 years in different trimesters of pregnancy, attending the ANC clinics as well as capable of reading and writing in the Arabic language.Results A total of 128 participants were enrolled. On conducting the receiver operating characteristic (ROC) analysis, the EPDS showed a larger area under the curve at 0.951 than the BDI-II tool (0.912). Using Youden’s index, a score >13 on the EPDS (87% sensitivity, 90% speciﬁcity) and >19 on the BDI-II (96% sensitivity, 73% speciﬁcity) allowed for the greatest division between depressed and non-depressed participants.Conclusion To address the under-recognition of antenatal depression, physicians at primary healthcare centres in Qatar should be encouraged to utilise the EPDS to screen pregnant women seeking ANC services.